2022
DOI: 10.1071/an21463
|View full text |Cite
|
Sign up to set email alerts
|

An attempt of using public ambient temperature data in swine genetic evaluation for litter-size traits at birth in Japan

Abstract: Context Large-scale genetic evaluation is promising for efficiently improving sow lifetime productivity, and therefore, a reasonable operational model should be pursued to analyse phenotypic data collected from around Japan, where unique seasonality exists. However, the information on establishing the model is currently insufficient. Aims To obtain the fundamental information on using ambient temperature information in developing the model for routine swine genetic evaluation in Japan, by analysing tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…According to this equation, ADG is expected to decrease by 12.6 g per 1°C increase in T when T > 21.1°C. Hara et al ( 2022 ) presented a scatter plot of the daily maximum temperatures in barns at the Japan National Livestock Breeding Center's Miyazaki Station and those at the Kobayashi station on the same day. When the daily maximum temperature at the Kobayashi station was 20°C, those at the Miyazaki Station were roughly in the range of 10°C to 20°C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to this equation, ADG is expected to decrease by 12.6 g per 1°C increase in T when T > 21.1°C. Hara et al ( 2022 ) presented a scatter plot of the daily maximum temperatures in barns at the Japan National Livestock Breeding Center's Miyazaki Station and those at the Kobayashi station on the same day. When the daily maximum temperature at the Kobayashi station was 20°C, those at the Miyazaki Station were roughly in the range of 10°C to 20°C.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the seasonal variation in temperature, and there may be a confounding or overlap in the phenotypic variability of ADG, which can be explained by these effects. Hara et al ( 2022 ) reported a positive correlation between the phenotypic variability for total number born, number born alive, and number still born explained by the farrowing season and month and that explained by the daily maximum temperature on the farrowing day (quadratic regression).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations